Methods of Calculating the Indexes of Intellectual Capital of Organizations - V. A. Korzhak (Статистика и экономика)
Competitive functioning at the micro and macro levels of businesses in different industries creates the need to make changes in the assessment of the impact on the performance of companies of tangible and intangible assets, leading to an increase in the value of both products and companies. In this context, it is appropriate to measure and evaluate intellectual capital, which includes not only goodwill, shares and intellectual property, but also organizational aspects (strategy, database, network data), and relationships with customers, partners, etc. Scientists and economists have studied the issues of defining and measuring intellectual capital for more than 30 years, however, there is no unified approach yet.This study presents the results of the analysis of approaches to the definition of the concept of “intellectual capital”, its components and methods of calculating the indexes of intellectual capital of organizations.The purpose of the study is to determine the direction of development of research concerning the calculation of indexes of intellectual capital on the value of organizations and indexes reflecting the state of individual elements and subelements of intellectual capital.Empirical base and research methods. The issues of measuring intellectual capital are reflected in the works of Edvinsson (1997), Sweibi (2010), assessing its impact on the value of companies and the effectiveness of their activities operating in the developed countries - Zegala (2010), Clark (2011), Liu (2017) - and developing countries - Garanina (2010), Bayburina, Bykova (2012), Andreeva (2016) [1, 5] and other scientists. The works of these researchers formed the basis of the research conducted in this article. This study used general scientific methods such as comparison, deduction, induction and analysis.Results. The paper presents the results of the analysis and systematization of approaches to the definition of “intellectual capital” and its components, methods for calculating its indexes and assessing their impact on the financial results of companies. Currently, there is also a need for research to assess the mutual influence of individual elements of intellectual capital. In order to identify the industry specifics of the impact of intellectual capital components on the value of organizations, the methods given in the article should be tested separately using data from companies from different industries. When conducting an analysis, it is important to take into account factors related to the external environment of the company, such as the level of economic development of the country in which the company operates, as well as fluctuations in economic activity.Conclusion. The practical value of the paper lies in the possibility of applying its results in the process of making managerial decisions of organizations in various fields. The proposed options for identifying and calculating indexes can significantly affect the financial growth of organizations, complementing traditional approaches to maintaining and compiling accounting and financial statements, thereby expanding their overall strategic development.